2020
DOI: 10.1007/s10389-020-01285-0
|View full text |Cite
|
Sign up to set email alerts
|

The interactive effect of gender, residence, and socioeconomic status on early sexual debut among sexually active young adults in Ghana

Abstract: Aim:The objective of this study was to examine the interactive effect of gender, rural-urban residence, and socioeconomic status on early sexual debut among young adults in Ghana Methods: The study used the 2014 Ghana Demographic and Health Survey with a sample of 2746 sexually active youth (males = 670 and females = 2076) aged 15-24. We used multivariate logistic regression to analyse the data.Results: Our results showed that female youth in urban areas and those from the wealthiest households were less likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Female children had higher odds of initiating sex early than male children. This finding supports earlier studies, which found females are more likely to initiate sex early than males [4,21,38]. Factors driving this phenomenon include early marriage, transactional sex, poverty and coercive sex [39,40].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Female children had higher odds of initiating sex early than male children. This finding supports earlier studies, which found females are more likely to initiate sex early than males [4,21,38]. Factors driving this phenomenon include early marriage, transactional sex, poverty and coercive sex [39,40].…”
Section: Discussionsupporting
confidence: 91%
“…Although there are studies on early sexual debut in Ghana, these studies have some limitations. First, these studies have focused on the youth [20,21] and women, especially those in their reproductive ages [22,23]. Second, these studies have emphasised the correlates of early sexual debut [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further exploration of these factors indicated that young people from rich households residing in urban areas are less likely to initiate early debut. However, an interactive effect showed that female youth residing in urban areas from rich households were more likely to initiate early debut (17). The extent to which socio-demographic characteristics influence consistent condom use among these sexually active young people remains unexplored within the Ghanaian context.…”
Section: Introductionmentioning
confidence: 99%